2019
DOI: 10.1145/3338810
|View full text |Cite
|
Sign up to set email alerts
|

Neural-network-based Memory for a Social Robot

Abstract: Many recent studies have shown that behaviors and interaction logic for social robots can be learned automatically from natural examples of human-human interaction by machine learning algorithms, with minimal input from human designers [1-4]. In this work, we exceed the capabilities of the previous approaches by giving the robot memory. In earlier work, the robot's actions were decided based only on a narrow temporal window of the current interaction context. However, human behaviors often depend on more tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To sum up, it can be seen that the current landscape preference analysis system of rural cultural tourism tourists with specific landscape preference as the database generally has the problems of poor recognition effect, low recognition accuracy, poor stability, and low data utilization rate in practical application [14][15][16]. On the other hand, in the existing landscape preference analysis system of rural cultural tourism tourists, the vast majority of identification methods can only identify a single rural cultural tourism and cannot identify rural cultural tourism with obvious differences, so they do not have the characteristics of intelligence [17][18][19]. In addition, the utilization rate and data mining effect of the obtained landscape preference data of rural cultural tourism tourists in the process of identification are also very poor [18].…”
Section: State Of the Artmentioning
confidence: 99%
“…To sum up, it can be seen that the current landscape preference analysis system of rural cultural tourism tourists with specific landscape preference as the database generally has the problems of poor recognition effect, low recognition accuracy, poor stability, and low data utilization rate in practical application [14][15][16]. On the other hand, in the existing landscape preference analysis system of rural cultural tourism tourists, the vast majority of identification methods can only identify a single rural cultural tourism and cannot identify rural cultural tourism with obvious differences, so they do not have the characteristics of intelligence [17][18][19]. In addition, the utilization rate and data mining effect of the obtained landscape preference data of rural cultural tourism tourists in the process of identification are also very poor [18].…”
Section: State Of the Artmentioning
confidence: 99%
“…An interesting method in the context of learning dialogue policies is applied by Doering, Kanda, & Ishiguro (2019). In their work, a physical scenario is configured to collect human-human interactions, which are then used to simulate speech interactions in purchasing scenarios.…”
Section: System Training Based On Human Empirical Datamentioning
confidence: 99%
“…Doering et al [10] focused on the problem of modeling the hidden structure of interaction, which enabled resolution of ambiguous customer speech. Doering et al [11] showed how gated recurrent neural networks could be used to learn a memory model of customer behavior. In addition, Doering et al [12] presented a system that could explore different robot behaviors and learn online, which resulted in more varied, interesting robot behaviors than previous approaches and enabled some customization to customers' individual differences.…”
Section: Data-driven Imitation Learning Of Social Interaction Behaviorsmentioning
confidence: 99%